In vitro regeneration through callus in pointed gourd (Trichosanthes dioica Roxb.) (Bangladesh Journal of Agricultural Research, 2010)
An efficient protocol was developed for in vitro plant regeneration and multiplication through callus culture in pointed gourd. Among the explants, highest percentage of cotyledon explants (92.00%) produced callus when this explant cultured in MS medium supplemented with NAA (0.1, 0.5, 1.0, 1.5, and 2.0 mg/l) and 2, 4-D (0.1, 0.5, 1.0, 1.5, and 2.0 mg/l). The highest number of shoots per explant was observed in MS + 0.5 mg/l BAP + 0.5 mg/l NAA followed by 1.0 mg/l BAP + 0.5 mg/l NAA when inter-node derived callus cultured in MS medium. Among the explants derived calli from leaf, inter-node and cotyledon in in vitro regeneration study, inter-node appeared as the most suitable explant for callusing and plant regeneration. The best response towards root induction was achieved on half MS medium supplemented with 0.5 mg/l NAA. The regenerated plantlets were successfully established in prepared earthen soil pot. Keywords: In vitro regeneration; pointed gourd. DOI: 10.3329/bjar.v35i3.6453Bangladesh J. Agril. Res. 35(3) : 465-473